2021
DOI: 10.1111/bjc.12293
|View full text |Cite
|
Sign up to set email alerts
|

Child abuse and suicidality in the context of the Interpersonal Psychological Theory of Suicide: A network analysis

Abstract: Objectives While there is evidence for an association of child abuse with suicidality in the course of life, the underlying mechanisms remain unclear. The Interpersonal Psychological Theory of Suicide (IPTS) provides a theoretical framework to investigate this relationship. The present study examines how different subtypes of child abuse are related to suicidal ideation and to attempts in the context of the IPTS. Methods 146 psychiatric inpatients (M = 37.9 years, 62% female) with an acute suicidal crisis (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 55 publications
3
16
0
Order By: Relevance
“…The present findings expand previous evidence of stronger overall associations between depression and emotional abuse (Krakau et al, 2021;Negele et al, 2015). They are also in line with previous network investigations underscoring the centrality of emotional abuse experiences within other contexts, such as suicidal crises (Schönfelder et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…The present findings expand previous evidence of stronger overall associations between depression and emotional abuse (Krakau et al, 2021;Negele et al, 2015). They are also in line with previous network investigations underscoring the centrality of emotional abuse experiences within other contexts, such as suicidal crises (Schönfelder et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…This study analysed data from a prospective multicentre study, longitudinally investigating predictors of suicidal ideation and behaviour over the course of 12 months. Further results from this study can be found elsewhere (Forkmann et al, 2020, b;furthermore: Brailovskaia et al, 2019;Höller et al, 2020Höller et al, , 2021Lucht et al, 2020;Paashaus et al, 2019Paashaus et al, , 2020Paashaus et al, , 2021Rath, Teismann, Hoeller, et al, 2021;Rath, Teismann, Schmitz, et al, 2021;Schönfelder et al, 2020Schönfelder et al, , 2021Teismann et al, 2021;Wannemueller et al, 2020). In the current examination, only data from the first assessment (T 0 ) were analysed.…”
Section: Participantsmentioning
confidence: 78%
“…Contrastingly, research in Brazil demonstrated contradictory findings that emotional neglect is directly associated with suicidal ideation; however, physical neglect and sexual abuse are not [ 21 ]. In a German network analysis, sexual abuse is the only sub-type of abuse directly related to suicidal ideation [ 22 ], whereas a recent meta-analysis shows that physical abuse has the strongest effect on suicidal ideation [ 23 ]. Compared with non-left-behind children, the left-behind children reported a high risk of suicidal ideation if they ever suffered any type of maltreatment [ 24 ].…”
Section: Literature Reviewmentioning
confidence: 99%